A mitigation technique for torque ripple in a brushless DC motor by controlled switching of small DC link capacitor - Bogimi Sirisha; Laxminarayana Yalakanti (Bulletin of Electrical Engineering and Informatics, 2022)
High performance applications are now days utilizing the brushless DC motor (BLDC) drives due to its ruggedness, compactness, high torque to weight ratio, high dynamic response etc. the feature of square-wave current excitation waveforms in BLDC motor drives allows some major system simplifications for trapezoidal BLDC motors. The developed torque is constant in ideal conditions in this motor when its back emf waveform is of trapezoidal type. Despite this, due to the physical construction of the motor and its settings, torque ripple exists in the output torque and is an undesired phenomenon in the BLDC motor drives and are also linked to the motor's control and driver sides. This paper provides a new way for reducing torque ripple and is simple, compact and cost effective. To prove the correctness of the compensation technique, circuit is modelled and simulations are carried to examine the theoretical performance of the BLDC motor drive. Experiments on a prototype drive were conducted to further validate the theoretical analysis as well as the utility of the proposed technique.